Evaluating the Role of Constitutional Amendments in Strengthening Democratic Governance in Indonesia - Irman Putra; Arief Fahmi Lubis (Westscience Press, 2023)
This study evaluates the role of constitutional amendments in strengthening democratic governance in Indonesia through qualitative juridical analysis. This research examines how amendments to the Indonesian Constitution since the Reform Era have affected the democratic process and governance structure. Key changes include the establishment of the Constitutional Court, direct presidential elections, and greater regional autonomy. The research findings show that while these amendments have contributed significantly to democratisation by improving the separation of powers, checks and balances, and the protection of human rights, there are still some challenges to effective implementation. The study concludes with recommendations for further reforms to strengthen Indonesia's democratic governance framework.